Optimization of Solar Water Heating Systems for Enhanced Energy Efficiency Using Taguchi and Design of Experiments Methods - Abdulrahman DAUDA; Kafayat O. ADEYEMI; Musa T. ZARMAI, (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
Due to unreliable electricity supply in North-Central Nigeria, optimizing solar water heating (SWH) systems is critical to enhancing domestic energy efficiency and meeting household hot water needs. This study was motivated by the need to address inconsistent hot water availability and reduce dependence on fossil fuel-based heating. By acquiring and analyzing performance data from existing systems, the research employs advanced simulation tools, including MATLAB, to evaluate key design parameters such as collector area, insulation thickness, tilt angle, and flow rate. Using the Taguchi optimization method and Design of Experiments (DOE), the study systematically explores the impact of these factors on system performance. The results reveal significant improvements, with optimized systems achieving a consistent thermal efficiency of 60%, compared to baseline efficiencies ranging from 5% to 70%, depending on time of day and climatic conditions. Optimal settings included a collector area of 0.95 m², tilt angle of 25.5°, and a flow rate of 0.17 m/s, with outlet temperatures 2.5–4 °C higher than baseline models. Energy output increased by an average of 35% over the tested time series. These gains demonstrate the potential for energy savings and reduced greenhouse gas emissions, underscoring the importance of robust design parameters and providing actionable insights for improving SWH systems for widespread adoption in Nigeria. This research contributes to the growing body of knowledge on renewable energy solutions, offering a pathway for sustainable energy use in households.